Risk factors for delayed immunization among children in an HMO. - Lieu, T A (1994)
OBJECTIVES. Improving the timely delivery of childhood immunizations has become a national imperative. This study aimed to identify nonfinancial predictors of delayed immunization among patients with good financial access to preventive care. METHODS. This prospective cohort study used telephone interviews and a computerized immunization tracking system to evaluate 13-month-old children (n = 530) in a regional group-model health maintenance organization. RESULTS. More than one third of parents interviewed did not know when the next immunization was due. Thirteen percent were late for the measles-mumps-rubella immunization, recommended at 15 months of age, by 90 days or more. Independent predictors of delayed immunization included having a larger number of children (odds ratio [OR] = 1.4, P < .01), not having a regular doctor (OR = 2.9, P < .05), not knowing when the shot was due (OR = 2.0, P < .01), and not worrying about the risks of shots (OR = 1.4, P < .05). CONCLUSIONS. Financial access alone does not guarantee timely childhood immunization. In managed care settings, which may cover increasing numbers of children under health care reform, interventions are needed to better inform parents of when immunizations are due.